Chelsea the congratulations fairy - Meadows, Daisy (Meadows, Daisy. Rainbow magic special edition., 2015)
When Jack Frost steals Chelsea the Congratulations Fairy's magic items, no one can celebrate special occasions, and it is up to Rachel and Kirsty to help retrieve them.